The Effect of Madrasah Head Leadership Style and Work Motivation on Work Discipline of Madrasah Aliyah Teachers - Elvasusanti Elvasusanti; Syamsudduha Syamsudduha; Ulfiani Rahman (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
The purpose of this study was to discuss the influence of the leadership style of Madrasah heads and work motivation on the work discipline of Madrasah Aliyah teachers in the North Polongbangkeng District of Takalar District. This study aims to determine the effect of Madrasah head leadership and work motivation on the work discipline of Madrasah teachers. This study uses a type of descriptive and inferential quantitative research. Data collection techniques used in this study were observation, questionnaire and documentation. The population in this study were 101 teachers, with a total sample of 30 teachers from 101 teachers of Madrasah Aliyah Manongkoki, Madrasah Aliyah Muhammadiyah Palleko, Madrasah Aliyah Tarbiyah Islamic Boarding School and Assalam Islamic Boarding School Madrasa in Polongbangkeng District North Takalar District. Based on the results of this study, it is known that the style of Madrasah head leadership has a significant effect on the work discipline of Madrasah Aliyah teachers in Polongbangkeng District. This means that leadership styles must be effective in order to influence the work discipline of teachers. Work motivation towards work discipline of Madrasah Aliyah teachers in Polongbangkeng Subdistrict, if the discipline wants to be improved, the motivation of the teacher's work must also be increased. Together, leadership style and work motivation have a significant effect on the work discipline of Madrasah Aliyah in Polongbangkeng District.